A diachronic-synchronic review of gender in English - Fernández Domínguez, Jesús (Alicante Journal of English Studies / Revista Alicantina de Estudios Ingleses, 2007)
Why does man occur more frequently in the English language than woman does? Has the expression of gender evolved through the centuries or is it a non-changing linguistic universal? To what extent are inflections and word-formation processes able to convey gender in present-day English? This paper reviews a number of questions which have raised interest among scholars for many years, and which can now be reconsidered from a 21st-century perspective. To this end, the expression of gender is examined and illustrated from Old English to contemporary English to observe the alternatives which language provides and the differences in each of the periods covered. This allows taking a broad view of the state of the art, which seems necessary for an understanding of how biological sex can be expressed in the English language.